2012
DOI: 10.1039/c2fo10244g
|View full text |Cite
|
Sign up to set email alerts
|

Weight reduction effects of a black soy peptide supplement in overweight and obese subjects: Double blind, randomized, controlled study

Abstract: The present study determined the effect of black soy peptide supplementation on body weight and body fat in overweight/obese subjects. In a double-blind controlled trial, participants (n = 80) were randomized to either soy peptide supplementation (the test group) or to a placebo (the placebo group). Sixty-four people completed the study, and anthropometric parameters, serum inflammatory markers, and leptin and lipid profiles were measured. After 6 weeks, the test group (n = 35) had significant reductions in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…9,10 Recent studies have examined the safety and antioxidative and anticarcinogenic effects of black soybean pigment, but the antiobesity effects of anthocyanins in black soybean have not yet been shown. [11][12][13][14] We observed antiobesity and lipid-lowering effects in anthocyanin-rich black soybeans that were consistent with those of previously published studies. 15 We conducted an in vitro study before performing a randomized clinical trial and found that black soybean testa extracts (BBT) inhibited fat accumulation and related factors such as peroxisome proliferator-activated receptor gamma (PPARc) and CCAAT enhancer binding protein alpha (C/EBPa) in adipocytes induced from preadipocytes.…”
Section: Introductionsupporting
confidence: 94%
“…9,10 Recent studies have examined the safety and antioxidative and anticarcinogenic effects of black soybean pigment, but the antiobesity effects of anthocyanins in black soybean have not yet been shown. [11][12][13][14] We observed antiobesity and lipid-lowering effects in anthocyanin-rich black soybeans that were consistent with those of previously published studies. 15 We conducted an in vitro study before performing a randomized clinical trial and found that black soybean testa extracts (BBT) inhibited fat accumulation and related factors such as peroxisome proliferator-activated receptor gamma (PPARc) and CCAAT enhancer binding protein alpha (C/EBPa) in adipocytes induced from preadipocytes.…”
Section: Introductionsupporting
confidence: 94%
“…Details on the general characteristics of all volunteers subjects, which were recruited by public advertisement and the diet intervention protocol for obesity by BSP, are provided in our previous paper [15]. The study subjects were 34 overweight/obese subjects aged 19–65, who were interested in losing weights.…”
Section: Methodsmentioning
confidence: 99%
“…Serum leptin levels were found to be significantly reduced in these research participants [15]. BSPs used for the experiment are analogues of doenjang (fermented soybean paste) peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The control group (n ¼ 46) received pouches containing casein that had a similar appearance to that of the black soy peptide tablet. Kwak et al 11 conducted a pilot study in 32 subjects with fasting glucose X90 mg dl À1 dl; black soy peptide (1.5 g, 3.0 g or 4.5 g, dose-dependently) and placebo was randomly provided to study participants. From this study, high dose of the black soy peptide group (4.5 g day À1 ) showed a greater tendency of reduction in body weight (1.1±0.92 kg) than the other groups (data unpublished).…”
Section: Interventionmentioning
confidence: 99%